Do MOOCs Make You More Marketable? An Experimental Analysis of the Value of MOOCs Relative to Traditional Credentials and Experience - Mariela J. Rivas; Rachel B. Baker; Brent J. Evans (SAGE Publishing, 2020)
Massive open online courses (MOOCs) are marketed as opportunities for participants to improve their labor market outcomes, and tens of thousands of students have paid for career-focused MOOC certificate programs. However, there is limited and conflicting research on MOOCs and labor market outcomes. Using two randomized control trials, we test Amazon's Mechanical Turk respondents' preferences for hiring hypothetical freelance web developers. In the first experiment, we examine preferences for profiles with MOOCs as compared to profiles with traditional degrees (bachelor's, associates, and community college certificates). Respondents preferred all traditional degrees over a MOOC; MOOCs do not serve as substitutes for traditional postsecondary credentials. In the second experiment, we examine preferences for MOOCs as compared to no listed credential. Results demonstrate a 61-percentage point preference for MOOC credentials compared to no MOOC credential; the preference does not vary across levels of professional experience.